Peanut crop nutrition and yield in no-tillage system in succession to cover crops growth - Crusciol, Carlos Alexandre Costa; Soratto, Rogério Peres (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate cover crops shoot dry matter production and nutrients accumulation and the effect of straw mulch mechanical management on the dry season peanut crop nutrition and yield, in no-tillage system. The experiment was carried out on a dystroferric Hapludox, in Botucatu, SP, Brazil. A randomized blocks design, in a splitplot array, with four replications, was used. The plots were composed by cover crops: palisadegrass – Brachiaria brizantha cv. Marandu; pearl millet – Pennisetum glaucum cv. BN 2; and guineagrass – Panicum maximum cv. Mombaça. The subplots were composed by absence or presence of straw mulch mechanical management, by horizontal crusher use, 20 days after chemical management. Pearl millet presented the largest shoot dry matter production and the lowest nutrient contents, 71 days after emergence, in comparison with palisadegrass and guineagrass. The cover crops presented similar nutrients accumulation in shoot. The cover crops species and straw mulch mechanical management does not affect the peanut leaves nutrient contents and yield in no-tillage system.